2022
DOI: 10.3389/fonc.2022.930065
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence-guided laparoscopic hepatectomy versus conventional laparoscopic hepatectomy for hepatocellular carcinoma: A single-center propensity score matching study

Abstract: BackgroundIndocyanine green fluorescence-guided laparoscopic hepatectomy (ICG-guided LH) is increasingly used for the treatment of hepatocellular carcinoma (HCC). However, whether ICG-guided LH can improve surgical outcomes remains unclear. This study aimed to investigate the short-term outcomes and survival outcomes of ICG-guided LH versus common laparoscopic hepatectomy (CLH) for HCC.MethodsWe conducted a retrospective analysis of 104 ICG-guided LH and 158 CLH patients from 2014 to 2020 at our center. To avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…A total of six studies [ 25 27 , 29 31 ] provided data on the postoperative overall complications rate, revealing a rate of 27.6% (66/239) in the ICG group and 25.4% (75/295) in the non-ICG group. Although there was moderate heterogeneity ( I 2 = 22%, P = 0.27), the analysis indicated no significant disparities between the two groups (OR = 0.96, 95% CI 0.53–1.76, P = 0.9) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six studies [ 25 27 , 29 31 ] provided data on the postoperative overall complications rate, revealing a rate of 27.6% (66/239) in the ICG group and 25.4% (75/295) in the non-ICG group. Although there was moderate heterogeneity ( I 2 = 22%, P = 0.27), the analysis indicated no significant disparities between the two groups (OR = 0.96, 95% CI 0.53–1.76, P = 0.9) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding postoperative bleeding, data from five studies [ 25 27 , 29 , 30 ] showed a rate of 3.1% (6/191) in the ICG group and 2.1% (5/235) in the non-ICG group. In terms of postoperative liver failure, four studies [ 25 27 , 29 ] reported an incidence of 4.3% (6/141) in the ICG group and 2.7% (5/185) in the non-ICG group.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the challenges posed by disoriented vascular structures, our increased experience in hepatectomy enables us to rapidly adapt and comprehend these changes through a comprehensive preoperative review. Additionally, the use of repeat intraoperative ultrasound and ICG (indocyanine green) scope navigation assists in correlating preoperative imaging with intraoperative structural changes, ensuring greater surgical precision [22].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of ICG fluorescence laparoscopy over conventional laparoscopy is the ability to detect micrometastases and satellite lesions during surgery [ 23 , 24 ]. Intraoperative detection and management of micrometastases other than primary lesions are very important for patient prognosis.…”
Section: Discussionmentioning
confidence: 99%